STUDI KANDUNGAN LOGAM BERAT TEMBAGA (Cu) DAN TIMBAL (Pb) DI PERAIRAN DANAU TOBA, PROVINSI SUMATERA UTARA (Study of Heavy Metal of Copper (Cu) and Lead (Pb) in Lake Toba, North Sumatera Province) - Hiras Sucipto Tampubolon; Darma Bakti; Indra Lesmana (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2013)
The Purpose of Lake Toba were very diverse and required water qualityand fulled certain requirements. Otherwise, the used of the lake for the variousactivities of the society also gave impact to water quality degradation. Thisresearch were conducted from May to July 2013 in Lake Toba. This research usedPurpossive Random Sampling. There were 3 locations. Station I: Ajibata area,Station II: Haranggaol area and Station III: Porsea as the outlet of Lake Toba.Sampling activities were conducted once/month. This research aimed to knewheavy metal consentrate of Lead (Pb) and Copper (Cu) in water and sediment.This results showed indicated chemical physics parameter of Lake Tobastilled in the normal range. Concentrations of copper (Cu) in the water column ateach station in sequence 0.027 mg/l, 0.025 mg/l, 0.033 mg/l and the concentrationof lead metal (Pb) in the water column 0.039 mg/l, 0.014 mg/l, 0.029 mg/l. Whilemetal concentrations of copper (Cu) in sediments at each station in sequence1.092 mg/kg, 2.85 mg/kg, and 2.483 mg/kg and the concentration of lead metal(Pb) of 3,058 mg/kg, 3.592 mg/kg and 2,833 mg/kg. These results indicated theconcentration of heavy metal Cu and Pb in the water column had exceeded thequality standard, while concentrations of Cu and Pb in sediments had notexceeded the quality standard.Keyword: Cuprum (Cu), Lead (Pb), Toba Lake, Water Quality